UNREGISTERED POLYGAMOUS MARRIAGE: A SOCIO-LEGAL STUDY IN POMBEWE VILLAGE, INDONESIA - Fakhri Ramdani; Sapruddin; Hamiyuddin (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2026)
This study examines the practice of unregistered polygamous marriage (poligami siri) in Pombewe Village, Sigi Biromaru District, through the lens of Indonesian positive law and socio-legal reality. Employing an empirical juridical method with a socio-legal approach, data were collected through in-depth interviews with community members, husbands who contracted unregistered polygamous marriages, and their legal wives, and analyzed qualitatively. The findings reveal that unregistered polygamous marriage persists despite clear legal requirements under Law Number 1 of 1974 on Marriage mandating Religious Court approval and formal registration. Its persistence is driven by economic pressures, deteriorating domestic relations, selective religious interpretation, and the deliberate circumvention of the legal wife's consent. Sociologically, the practice inflicts compounding harm: psychological distress and social stigma upon the legal wife, legal and social uncertainty for the unregistered wife, and administrative obstacles and discrimination for children of such unions. Legally, the practice violates Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law, rendering the marriage without legally recognized consequences for all parties under the national legal system.